Pengaruh Metode Bermain Cerita Menyanyi (BCM) Terhadap Motivasi Belajar Siswa Pada Pembelajaran Pkn Siswa Kelas III - Elisa Indriyani; Ramanata Disurya; Adrianus Dedy (Universitas Pahlawan Tuanku Tambusai, 2023)
Abstract Posttest only control research design. The population in this study amounted to 39 students. The sample in this study amounted to 39 students consisting of class III A as the experimental class totaling 22 students and class 3 B as the control class totaling 17 students. The data collection technique used was a questionnaire (questionnaire). The data analysis technique used is the t test (independent sample t test). From the results of processing research data with the help of the SPSS application, it is obtained value = 3.774 and value = 1.687 with α = 0.05 and df = 37, then 3.774 ≥ 1.687 thus ≥ . In accordance with the criteria for testing the hypothesis, it is rejected and accepted. This shows that there is an influence of playing singing story method (BCM) on student learning motivation in class III student civics learning.